Self-efficacy in elderly with type 2 Diabetes Mellitus - Mariana Campos de Sousa; Bruna Stephanie Sousa Malaquias; Suzel Regina Ribeiro Chavaglia; Rosali Isabel Barduchi Ohl; Fabiana Fernandes Silva de Paula; Karina Santos da Silva; Álvaro da Silva Santos
ABSTRACT Objective: to analyze the self-efficacy of elderly with type 2 diabetes mellitus and the relationship with sociodemographic, clinical, knowledge, and attitude variables. Method: a cross-sectional quantitative study conducted with 256 elderly people enrolled in Family Health Strategies. Data were obtained through interviews. Descriptive statistical analysis and multiple linear regression model were performed (p <0.05). Results: female, 69.95-year mean age, white skin color, 4-7 years of schooling, living with a partner, retirees, low individual monthly income, 6 to 15 years of illness, Catholics, living with children (with or without spouse). The elderly's low knowledge and negative attitude prevailed. Self-efficacy was associated with attitude and knowledge in the domains "General and Specific Diet", "Physical Exercise" and "Blood Glucose". Conclusion: self-efficacy investigations in type 2 Diabetes Mellitus management in the elderly are important and encourage treatment adherence.